2015
DOI: 10.1098/rspb.2014.2820
|View full text |Cite
|
Sign up to set email alerts
|

Expression of parasite genetic variation changes over the course of infection: implications of within-host dynamics for the evolution of virulence

Abstract: How infectious disease agents interact with their host changes during the course of infection and can alter the expression of disease-related traits. Yet by measuring parasite life-history traits at one or few moments during infection, studies have overlooked the impact of variable parasite growth trajectories on disease evolution. Here we show that infection-age-specific estimates of host and parasite fitness components can reveal new insight into the evolution of parasites. We do so by characterizing the wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 42 publications
3
89
0
Order By: Relevance
“…P. ramosa Metchnikoff is a common Gram‐positive bacterial pathogen of D. magna found across the Northern Hemisphere (Ebert et al, ). During the course of infection, P. ramosa supresses reproduction of its host, causes pathogen‐induced gigantism and severely reduces host lifespan, before releasing millions of spores into the environment at host death (Clerc et al, ; Ebert et al, ; Hall & Ebert, ). Thus, transmission is exclusively horizontal in this system and depends on a balance between the virulence of the pathogen and its production of mature transmission spores (see Hall & Mideo, ).…”
Section: Methodsmentioning
confidence: 99%
“…P. ramosa Metchnikoff is a common Gram‐positive bacterial pathogen of D. magna found across the Northern Hemisphere (Ebert et al, ). During the course of infection, P. ramosa supresses reproduction of its host, causes pathogen‐induced gigantism and severely reduces host lifespan, before releasing millions of spores into the environment at host death (Clerc et al, ; Ebert et al, ; Hall & Ebert, ). Thus, transmission is exclusively horizontal in this system and depends on a balance between the virulence of the pathogen and its production of mature transmission spores (see Hall & Mideo, ).…”
Section: Methodsmentioning
confidence: 99%
“…These five pathogen genotypes vary considerably in virulence (i.e., the reduction of host lifespan) and production of transmission spores (Clerc et al. ; Hall and Mideo ).…”
Section: Methodsmentioning
confidence: 99%
“…After 20 days (at which point all surviving Daphnia will have produced mature transmission spores, Clerc et al. ), all surviving Daphnia (infected and uninfected) were collected, checked for infection under a dissecting microscope, and frozen individually as described above. Spore loads of infected animals were later quantified using an Accuri C6 flow cytometer (BD Biosciences, San Jose, California) following standard procedures as outlined in Gipson and Hall, ().…”
Section: Methodsmentioning
confidence: 99%
“…), and the relationship between pathogen virulence and transmission (Clerc et al. ; Izhar and Ben‐Ami ), depend on the age of the host, indicating that the optimal infectivity and virulence strategy for a pathogen may be age‐specific. In turn, research has shown that males are more resistant to infection, that mean pathogen fitness is greater within the female host (Duneau et al.…”
Section: Introductionmentioning
confidence: 99%